Effects of Internal Bremsstrahlung on Tritium Profile Reconstruction in BIXS Measurements. (1st November 2016) - Chen, Zhilin; Matsuyama, Masao; Abe, Shinsuke; Peng, Shuming
Abstract: Beta-induced X-ray spectrometry (BIXS) is a nondestructive method to detect tritium both on the surface and in the bulk of materials. The effects of internal bremsstrahlung (IB) from the beta decay of tritium on tritium profile reconstruction have been theoretically studied by numerical simulation based on Matlab code. Three kinds of samples, two polymers [(T-C4 H6 O2 )n, Zeff = 6.4, homogeneous and heterogeneous] and one zirconium, with different tritium depth profiles were used in the calculations, and two of them were confirmed by experiments. The results indicate that the intensity of IB is comparable with external bremsstrahlung (EB) for low-Z materials, and the intensity of IB decreases a little faster than that of EB for the same material. Neglecting IB would lead to as much as 12% counts loss in tritium profile reconstruction for a polymer sample, and it is expected to be more serious for lower-Z materials such as beryllium and carbon fiber composites. The results also show that for the same material, the influence of IB depends on the depth profile of tritium in the sample.